The Persistence of Silodosin Monotherapy and the Reasons for Withdrawal from Treatment of Previously Untreated Japanese Patients with Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia - Yoshinori Tanaka; Yasushi Tanuma; Naoya Masumori (Advances in Urology)
Objectives. The persistence of silodosin and the reasons for withdrawal from treatment of previously untreated Japanese patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH) were evaluated in real-life clinical practice. Methods. A total of 81 previously untreated Japanese patients diagnosed with LUTS/BPH were treated with silodosin monotherapy and prospectively followed for 4 years. The persistence rate was estimated using the Kaplan-Meier method. If silodosin had to be terminated or a patient did not come to the hospital, the reason was determined. Results. The 6-month, 1-year, 2-year, 3-year, and 4-year persistence rates were 63.0%, 56.8%, 50.6%, 44.4%, and 35.8%, respectively. The most frequent reason (22.2%) for withdrawal was symptom resolution. After silodosin treatment, the international prostate symptom score and the quality of life index were significantly improved and maintained for 4 years. Conclusions. 35.8% of previously untreated Japanese patients continued silodosin for 4 years. Many patients terminated silodosin for various reasons, the most frequent of which was symptom resolution. The effects of silodosin were maintained when the patients continued treatment. Trial Registration. This study was approved by the institutional review board of Hokkaido Prefectural Esashi Hospital (number 2007-2) and was registered in a public trial registry (UMIN000026910).